Implementation of Conditional Phase Gates Based on Tunable ZZ Interactions - Collodo, Michele C.; Herrmann, Johannes; Lacroix, Nathan; Andersen, Christian Kraglund; Remm, Ants; Lazar, Stefania; Besse, Jean-Claude; Walter, Theo; Wallraff, Andreas; Eichler, Christopher (Physical Review Letters, 2020)
High fidelity two-qubit gates exhibiting low cross talk are essential building blocks for gate-based quantum information processing. In superconducting circuits, two-qubit gates are typically based either on rf-controlled interactions or on the in situ tunability of qubit frequencies. Here, we present an alternative approach using a tunable cross-Kerr-type ZZ interaction between two qubits, which we realize with a flux-tunable coupler element. We control the ZZ-coupling rate over 3 orders of magnitude to perform a rapid (38 ns), high-contrast, low leakage (0.14±0.24%) conditional phase CZ gate with a fidelity of 97.9±0.7% as measured in interleaved randomized benchmarking without relying on the resonant interaction with a noncomputational state. Furthermore, by exploiting the direct nature of the ZZ coupling, we easily access the entire conditional phase gate family by adjusting only a single control parameter.
CRIS-Team Scopus Importer:2022-06-27